Raising achievement in secondary mathematics - Watson, Anne, 1948- (Maidenhead, England : Open University Press, 2006)
This book brings together research and professional knowledge to enhance the teaching of lower attaining students in secondary mathematics. Attainment in mathematics is an important social issue, since underachievement can make a difference to future life choices, particularly amongst certain groups of students. "Raising Achievement in Secondary Mathematics" shows how well-meant teaching strategies and approaches can in practice exacerbate underachievement in maths by making inappropriate demands on learners. As well as criticizing some of the teaching and grouping practices that are considered normal in many schools, the book also offers an alternative view of attainment and capability, based on real classroom incidents in which 'low attaining students' show themselves to be able to think about mathematics in quite sophisticated ways. The author argues that teaching could be based on learners' proficiency, rather than on correcting deficits in knowledge and behaviour.; She describes how a group of teachers who believed that their students could do better with higher expectations developed a range of principles and strategies to support their work - the students showed significant progress and the teachers felt they were doing a better job. With numerous case studies, ideas and teaching strategies, this book is for anyone who is teaching, or learning to teach, mathematics.
Learning about school mathematics -- Abilities and understanding -- Teacher's judgments -- The impact of differences in practice and belief -- The fallacy of 'getting to know' learners -- Thinking mathematically in low-attaining groups -- Approaches to reconstruction: test cramming versus developing proficiency -- Identifying deep progress -- Construction, reconstruction and renewal.
Includes bibliographical references (pages 176-186) and indexes.
BIED
Complimentary copy from BIED
Keywords: Mathematics -- Study and teaching (Secondary); Effective teaching; Effective teaching; Mathematics -- Study and teaching (Secondary); Mathematics -- Teaching -- Secondary schools